2014
DOI: 10.1155/2014/139826
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Exfoliation Syndrome in the Central Anatolia Region of Turkey

Abstract: Aim. The aim of this study was to investigate the frequency of exfoliation syndrome in the Central Anatolia region of Turkey and to evaluate its relationship with cardiovascular and ocular diseases. Methods. Patients over the age of 45 years who presented to the clinic were included in the study. All cases underwent a comprehensive ophthalmology examination. Exfoliation syndrome was diagnosed with the presence of exfoliative material on the lens anterior capsule or iris on slit lamp examination. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
4
3
2
Order By: Relevance
“…The XFS prevalence was 6.5% for the 45 years and older population in this study but 10.1% in the previous hospital‐based study (Kılıç et al. ). The higher rate in the hospital‐based study could be due to the increased presentation of exfoliative glaucoma patients at the hospital for their routine follow‐ups compared to normal subjects.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…The XFS prevalence was 6.5% for the 45 years and older population in this study but 10.1% in the previous hospital‐based study (Kılıç et al. ). The higher rate in the hospital‐based study could be due to the increased presentation of exfoliative glaucoma patients at the hospital for their routine follow‐ups compared to normal subjects.…”
Section: Discussioncontrasting
confidence: 80%
“…We found XFS to be more common in males in this study as in the previous hospital‐based one and the difference was statistically significant (Exp(B): 1.91 OR: 1.88, CI: 1.08–3.39 p = 0.027) (Kılıç et al. ). Some studies reported higher rates in both genders but most found no significant relationship between gender and XFS (Kozobolis et al.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations